Examing Determinants of High School Students’ Satisfaction and Learning Outcome in Heilongjiang, China - Shi, Ji (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study aims to examine the factors influencing the satisfaction of 4th-year high school students in Heilongjiang Province, China. Gaining insights into these factors will help improve the overall quality of education and student experience. Research design, data and methodology: A quantitative research design was employed, using survey data collected from a sample of 550 male 4th-year high school students in Heilongjiang Province. The questionnaire assessed variables such as the quality of academic staff, school facilities, curriculum relevance, and student support services. Structural equation modeling (SEM) was used to analyze the relationships between these factors and student satisfaction. Results: The analysis has shown that all proposed factors positive influence overall satisfaction, by having student support services, school’s reputation, and the quality of programs as the greatest contributors. The research framework demonstrated strong reliability, with factor loadings and goodness-of-fit indices meeting acceptable thresholds. Conclusions: The findings suggest that improving access to resources, enhancing academic programs, and building institutional reputation are key strategies for increasing both student satisfaction and learning outcomes in high schools. Educational policymakers should focus on these areas to foster a more engaging and fulfilling learning experience for students.